Влияние магнитных полей 1,5–50 Гц на концентрацию ионов кальция и магния в головном мозге мышей - Нецветов, М.В.; Хиженков, П.К.; Энглези, А.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The goal of our research was to determine the influence of low magnetic fields on the concentration of Ca2+ and Mg2+ ions in the brain tissue of experimental mice. During the experiment, one group of animals was kept intact (group 1), another one drank MgSO4 10% solutions instead of water (group 2) or CaCl2 10% solution (group 3), and the fourth one was with experimental brain injury and drank water (group 4). All of them were treated with magnetic fields H = 30
Oe and different low frequencies. Control animal groups were observed out of the magnetic field. The effect of magnetic fields on intact mice varies, by depending on the frequency. The dependence of [Ca2+] on the field frequency doesn’t alter much. But the dependence of [Mg2+]
on the frequency is different under different experimental conditions.